Memadukan Budaya Hukum dan Diplomasi Hukum untuk Mencegah Sengketa Antar Negara: Kekosongan Hukum yang Terabaikan - Birahayu, Dita (Faculty of Law Hang Tuah University, 2024)
Efforts to integrate legal culture and legal diplomacy to prevent conflicts between countries are a noble goal. However, these efforts are characterized by various legal complexities, including neglected legal vacuums. This legal vacuum can be a legal loophole for countries to exploit the international legal system and trigger disputes. This research aims to analyze the concept and meaning of legal culture and legal diplomacy, examine its role and function in preventing conflicts between countries, and analyze the effectiveness of its integration. This study uses a normative juridical research method with a conceptual and a comparative legal approach. The results of the study show that legal culture and legal diplomacy have an important role and function in preventing conflicts between countries. The combination of the two can help build trust and mutual understanding between countries, increase public legal awareness, and encourage peaceful settlement of disputes in accordance with the Preamble of the UN Charter.